Pengaruh Pengalaman Kerja Kompetensi Independensi Motivasi Dan Etika Auditor Terhadap Kualitas Audit Pada Kantor Bpk Perwakilan Provinsi D.I. Yogyakarta - Rahmawati, Gustin, Drs. Wahyono, M.A., Akt (2017)
This study aimed to determine the effect of work experience, competence, independence, motivation and ethics of auditors on audit quality in the office of the CPC representative. This study was a quantitative research. The sample is determined by the method of convience and obtained 31 respondents. Analysis of data using multiple linear regression with SPSS version 17. The results of this study indicate that work experience, competence, independence and ethics affect the quality of the audit, while the motivation does not affect the quality of the audit.